PENYELESAIAN SENGKETA PENETAPAN KAWASAN HUTAN BERDASARKAN PRINSIP HAK MENGUASAI NEGARA DI DESA SUKAWANGI: Settlement of Disputes over Forest Area Designation Based on the Principle of the State’s Right to Control in Sukawangi Village - Pinkan Nur Ainiyah; Intan Nevia Cahyana (Reformasi Hukum Trisakti, 2026)
The dispute over the determination of forest areas and the principle of state control rights is a public law issue related to the legitimacy of government actions and their compliance with Article 33 paragraph (3) of the 1945 Constitution. The determination of forest areas in Sukawangi Village arose due to the issuance of a Decree of the Minister of Foresty which triggered a tenurial conflict. The formulation of the problem in this study is how the mechanism for determining forest areas based on Law Number 41 of 1999 and Government Regulation Number 23 of 2021 and how to resolve forest area disputes based on the principle of state control rights through social forestry policies. Using empirical juridical research methods, data were collected through document studies and field observations. The results of the study indicate that the determination of forest areas in Sukawangi Village does not fulfill the principle of justice as stipulated in Article 2 letter c of Law 41/1999, the principle of participation and openness based on Article 68 paragraph (2) of Law 41/1999 in conjunction with Article 96 of Government Regulation No. 23/2021, and the principle of legal protection because the community is not involved in  determination process.